Comparative Study of Calix-6-arene, 2-Hydroxy Propyl Beta Cyclodextrin and 18-Crown-6 as Ionophores in Potentiometric Ion-Selective Electrodes for Determination of Trigonelline in Trigonella foenum-graecum Seeds Extract and Plasma - Maha. F. Abdel Ghanya, Lobna. A. Husseina, Hend. Z. Yamania (Journal of Applied Pharmaceutical Science, 2014)
The present work evaluates the influence of Calix-6-arene, 2-hydroxy propyl β-cyclodextrin and 18-crown-6 as ionophores on the fabrication of trigonelline selective electrodes 1, 2 and 3, respectively. The three proposed sensors showed Nernstian slopes of 59, 60 and 55.75 mV/concentration decades over pH range 4-9 for sensors 1, 2 and 3, respectively. Both sensors 1 and 2 covered the concentration range 10-3 – 10-5 M, while sensor 3 showed linear response over the range 10-2 – 10-4 M. The proposed sensors offer the advantages of fast response and moderate stability time. The selectivity coefficients of the developed sensors indicated excellent selectivity for trigonelline. The proposed electrodes were successfully applied for direct determination of trigonelline in pure form, Trigonella foenum-graecum seeds extract and plasma without prior separation or pretreatment steps. The proposed sensors can be used in quality control labs and in clinical trails for routine analysis of trigonelline in Trigonella foenum-graecum seeds extract and plasma.
Keywords: Ion selective electrodes, ionophores,trigonelline, Trigonella foenum-graecum,plasma.